1999
DOI: 10.1007/s11325-999-0083-7
|View full text |Cite
|
Sign up to set email alerts
|

Snoring and Sleep Apnea in Obese Adolescents: Effect of Long-term Weight Loss-Rehabilitation

Abstract: Objective: To test the effect of a long-term weight loss rehabilitation program in extremely obese adolescents on breathing parameters during sleep. Methods: Thirty-eight extremely obese [mean body mass index (BMI) 45.3 +/- 7.9kg/m(2)] adolescents participated during a three- to nine-month period in an inpatient weight loss rehabilitation in a specialized long-term rehabilitation center. Breathing parameters were registered via a seven-channel portable screening device. Body weight and arterial blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 23 publications
(24 reference statements)
0
21
3
4
Order By: Relevance
“…This result is in agreement with the results of Siegfried et al and Verhulst et al, studies that also evaluated adolescents submitted to a weight loss therapy. 38,39 It is important to mention that SDB can worsen cognitive learning function. 33 Considering the age of the population studied, this might also have an important impact in school performance.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with the results of Siegfried et al and Verhulst et al, studies that also evaluated adolescents submitted to a weight loss therapy. 38,39 It is important to mention that SDB can worsen cognitive learning function. 33 Considering the age of the population studied, this might also have an important impact in school performance.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data from retrospective cohort studies generated from residential treatment centres or reports on bariatric surgery support this recommendation (class IV) [200][201][202]. The effects of weight loss on an outpatient basis have not been studied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[21–23] Same results are reflected in present cross sectional study, [Table 1] where the prevalence of snoring as surrogate of sleep disordered breathing was significantly lower in persons of BMI in normal range, as compared to those in range of pre obese or obese; but lack of significant difference, in prevalence of snoring among overweight and obese, points towards the fact that just by reduction of BMI from obese to pre obese range, is not enough to help the snorers. They in fact need to reduce their BMI to less than 25 kg/m 2 that is in normal range.…”
Section: Discussionmentioning
confidence: 99%
“…Sieqfried et al . [23] did their study on 38 extremely obese adolescents, and they concluded that weight reduction is good for OSA, but for snoring, its role might be overestimated. This difference could be explained by saying, that this study, was on comparatively lesser sample size, and subjects recruited were not adults.…”
Section: Discussionmentioning
confidence: 99%